Changing indications for a total pancreatectomy: perspectives over a quarter of a century. Issue 5 (19th November 2014) - Almond, Max; Roberts, Keith J.; Hodson, James; Sutcliffe, Robert; Marudanayagam, Ravi; Isaac, John; Muiesan, Paolo; Mirza, Darius
Abstract Introduction The indications for a total pancreatectomy (TP), its peri‐operative management, provision of pancreatic surgical services and medical treatment of the inherent exo‐ and endocrine deficient states have all changed considerably over recent decades. The effects of these upon the incidence, indications for and outcomes of TP are unclear. Patients undergoing TP at a single institution over a quarter of a century were reviewed to try to address these issues. Methods Data on patients who underwent elective (el‐) and emergency TP (em‐TP) between 1987 and 2013 were reviewed. Patient demographics, indications, intra‐operative details, peri‐operative management and long‐term outcomes were analysed. Absolute numbers of TP were reported relative to partial pancreatectomy rates. Results In total, 136 patients underwent TP [98 (72.1%) el‐TP; 38 (27.9%) em‐TP]. There was a significant change in indication for el‐TP with it increasingly performed for (an intraductal papillary mucinous neoplasm (IPMN) and renal cell metastases whereas there was a decrease in the number of el‐TP performed for chronic pancreatitis (P = 0.025). The relative rates of el‐TP, however, did not change significantly across the study period (P = 0.225). The median length of stay after el‐TP decreased from 19 days pre‐1997 to 12 days post‐1997 (P = 0.009). The relative use of em‐TP declined by 0.28 percentage points per year [P = 0.018; 95% confidence interval (CI): 0.04–0.41]. Conclusions The indications for el‐TP have changed; it is being performed more frequently although the proportion relative to other pancreatic resections has not changed. A decrease in the rate of em‐TP is likely to reflect improved peri‐operative management of a pancreatic fistula and its complications after a pancreaticoduodenectomy.